1994
DOI: 10.1136/hrt.72.4.339
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prophylaxis in permanent pacemaker implantation: a prospective randomised trial.

Abstract: Background-Pacemaker pocket infection is a potentially serious problem after permanent pacemaker implantation. Antibiotic prophylaxis is commonly prescribed to reduce the incidence of this complication, but current trial evidence of its efficacy is conflicting. A large prospective randomised trial was therefore performed of antibiotic prophylaxis in permanent pacemaker implantation. The intention was firstly to determine whether antibiotic prophylaxis is efficacious in these patients and secondly to identify w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 8 publications
3
53
0
1
Order By: Relevance
“…No cases of superficial infection occurred among the patients who received antibiotic prophylaxis. This finding is consistent with the results published by Monsey et al 18 in which skin erosion was the most common presentation.…”
Section: Discussionsupporting
confidence: 83%
“…No cases of superficial infection occurred among the patients who received antibiotic prophylaxis. This finding is consistent with the results published by Monsey et al 18 in which skin erosion was the most common presentation.…”
Section: Discussionsupporting
confidence: 83%
“…The occurrence of these 3 fatal events, as well as another 2 severe and 1 mild event, emphasizes that postoperative infections causing sepsis or endocarditis are not uncommon and carry an ominous prognosis in a defibrillator population; every effort should be undertaken to provide adequate preventive measures. Mounsey et al 13 showed a significant beneficial effect in patients receiving antibiotic prophylaxis before pacemaker implantation.…”
Section: Patient Deathsmentioning
confidence: 98%
“…Rates of wound infection were 3.2% and 6.5% for the clindamycin and cephalothin groups, respectively (not significant), with no cases of endocarditis. For pacemaker implantation, 48 h of flucloxacillin (or clindamycin in those who were allergic) was compared with placebo in a randomized trial of 473 patients undergoing first-ever permanent pacemaker placement (21). All nine serious infections occurred among those in the placebo group.…”
Section: Preoperative Prophylaxismentioning
confidence: 99%